Axial Movement Sensor Based on Chaotic Oscillator and Planar Coil - Timur Karimov (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2020)
Axial movement measurement is required in various technical tasks. In a range up to several centimeters, inductive sensors are widely used. However, cheap on-the-shelf sensors often suffer from low sensitivity. Instead of them, linear potentiometers, inductive sensors with moving cores, linear magnetic encoders or laser systems are used, but these solutions have their own limitations and higher costs. In this paper, we propose an inductive sensor consisting of a planar coil included in a chaotic circuit based on the Cang system. Coil inductance serves as a bifurcation parameter. When the target moves towards the coil and inductance accordingly changes, the phase volume of system attractor also changes. Nonlinearity of this system allows obtaining a steeper sensitivity characteristic comparing with a harmonic oscillator. The phase volume can be easily measured using analog means, which results in completely analog sensor design. We show that such a system is able to perform proximity measuring tasks with adjustable range and high accuracy.